Islamic Law View on Protecting the Rights of Housewives at Risk of Contracting HIV/AIDS - Thahir, Putri Shafarina; Al-Fatih, Sholahuddin (De Jure: Jurnal Hukum dan Syari'ah, 2024)
This article examines the perspective of Islamic law regarding the protection of the rights of housewives at risk of contracting HIV/AIDS from their husbands. Although HIV/AIDS is not a new issue, its impact on families, especially housewives, remains an essential concern in legal and public health contexts. Within the framework of Islamic law, individual rights, including women's rights, are guaranteed and need protection. This research uses normative legal and sociological research methods with a case approach. The results show that Islamic law has a vital role in protecting the rights of housewives who are at risk of contracting HIV/AIDS from their husbands. These rights include the right to know the husband's health status, the right to obtain protection, the right to refuse sexual relations, and the right to get a divorce. Islamic law places great responsibility on husbands to protect the health of their wives and families. Husbands are expected to maintain the welfare of their wives and families, including by taking preventive steps against the transmission of HIV/AIDS. Apart from that, Islamic law also emphasises the importance of fidelity in the husband-wife relationship. Husbands are expected to be faithful to their wives, which is also a preventive measure against the transmission of HIV/AIDS. If a husband fails to fulfil his responsibility to protect his wife from contracting HIV/AIDS, Islamic law gives the wife the right to seek protection, including through legal remedies such as requesting a fatwa from ulama or even filing a divorce petition. This research is expected to help increase public understanding of the rights of housewives at risk of contracting HIV/AIDS, as well as encourage efforts to protect their rights.